2017
DOI: 10.1016/j.mrgentox.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Personal samplers of bioavailable pesticides integrated with a hair follicle assay of DNA damage to assess environmental exposures and their associated risks in children

Abstract: Agriculture in the United States employs youth ages ten and older in work environments with high pesticide levels. Younger children in rural areas may also be affected by indirect pesticide exposures. The long-term effects of pesticides on health and development are difficult to assess and poorly understood. Yet, epidemiologic studies suggest associations with cancer as well as cognitive deficits. We report a practical and cost-effective approach to assess environmental pesticide exposures and their biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 57 publications
0
40
1
Order By: Relevance
“…One of the CEC’s primary goals is to reduce environmental disparities experienced by Pacific Northwest Tribes by developing collaborative community-engaged research between Oregon State University Superfund Research Program scientists and Tribes. The SITC invited the CEC to collaborate on air toxic monitoring projects that included using silicone passive sampling wristbands to measure personal chemical exposures [7,8,9]. This exposure assessment method is non-invasive, simple to use, and provides individual time-averaged exposure data [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the CEC’s primary goals is to reduce environmental disparities experienced by Pacific Northwest Tribes by developing collaborative community-engaged research between Oregon State University Superfund Research Program scientists and Tribes. The SITC invited the CEC to collaborate on air toxic monitoring projects that included using silicone passive sampling wristbands to measure personal chemical exposures [7,8,9]. This exposure assessment method is non-invasive, simple to use, and provides individual time-averaged exposure data [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As passive samplers, silicone wristbands work by chemical diffusion (absorption) of an environmental contaminant into the polymer of the silicone over time [4]. They were first introduced by O'Connell et al [5] in 2014 to assess exposure in an occupational setting, but have since been used in several studies, ranging from assessment of pesticide exposure among farmers in West Africa [6] and Peru [7] and flame retardant exposure among preschool children in the United States [4,8,9], to assessment of volatile organic chemicals emanating from the surface of human skin [10]. These studies have demonstrated that a commercial silicone wristband, worn by study participants, offers a non-invasive and simple way to quantify personal exposure to multiple chemicals from multiple microenvironments and within a multiday time period.…”
Section: Introductionmentioning
confidence: 99%
“…To date, silicone wristbands have been employed in a small number of studies to measure polycyclic aromatic hydrocarbons (PAHs) [5], polybrominated diphenyl ethers (PBDEs) and novel flame retardants (NFRs) [4,13], organophosphate esters (OPEs) [12], and pesticides [6,9]. However, these previous studies on wristbands were limited to one group of compounds or to qualitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed the links between residential and occupational exposure to pyrethroids and potential health effects. Vidi et al (179) reported a significant association between bifenthrin, cypermethrin, deltamethrin, cis-and trans-permethrin and DNA damage in the hair of residentially exposed children in farmer households. An observational study using data from poison control centres reported that the second most common pesticide group by exposure frequency were pyrethroids, and children aged ≤5 years were the group most at risk of exposure (180).…”
Section: Human Exposure To Pyrethroidsmentioning
confidence: 99%